Reconstruction of Expert Testimony For Determining The Judge Considering iIn The Corruption Case Based On Justice - Siti Nursyakirah Yuslan; Sera Rosanto (Universitas Islam Sultan Agung, 2019)
Calculation of state losses can only be done by an expert. Experts here are not only experts in the field of financial audit but also engineers who will calculate the feasibility of construction of a building in case of corruption was related to the construction field. Expert who has the competence do calculating the quantity of a building and the price of a building is a person who has a construction management certification. Judge in assessing the truth of the testimony / evidence, in the RIB in the know with 3 systems of evidence include; free system (Vrij Bewijk); positive system (wettellijk) and negative cystine (wettellijk). In the formulation of Article 184 paragraph (1) Criminal Procedure Code, which specified that legal evidence is: witness testimony; expert testimony; letter; pointing and testimony of the defendant. Each handling of corruption cases, the process of calculating the amount of state losses in practice are still causing differences of interpretation either by the Prosecutor, state audit agency (BPK), the financial supervision and development (BPK), as well as the court. Description Construction Experts who have no competence in the matter of corruption, the statement becomes invalid.Keywords: Reconstruction; Expert; Testimony; Corruption and Justice.